1994
DOI: 10.1068/p230321
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Moon Illusion: A Multifactor Angular Account

Abstract: It is argued that the failure to explain the celestial illusion results from conceptual confusion about perceived size and from disregard of the observational evidence relating to the natural moon illusion. The evidence shows that the illusion consists of a perceived angular size enlargement of horizon objects, by a factor of about 1.5-2.0 in diameter in comparison with elevated objects. Most measurements of the illusion have been made in terms of angular size, although in some proposed explanations an illusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This distal versus projected distinction has been made often in the visual perception literature (Arend & Goldstein, 1990;Carlson, 1960;Changizi & Widders, 2002;Gibson, 1950;Gilinsky, 1955;Gillam, 1998;Mack, 1978;Palmer, 1999;Rock, 1983;Sedgwick & Nicholis, 1993), and perception of projected size (as opposed to distal size) has been observed a number of times over the history of visual perception (Angell, 1974;Baird, 1968;Biersdorf, Ohwaki, & Kozil, 1963;Carlson, 1960Carlson, , 1962Craig, 1969;Daniels, 1972;Foley, 1972;Gibson, 1950;Gilinsky, 1955;Gogel & Eby, 1997;Jenkin & Hyman, 1959;Joynson, 1949;Kaneko & Uchikawa, 1993, 1997Komoda & Ono, 1974;Leibowitz & Harvey, 1969;Lucas, 1969;Mack, 1978;McCready, 1965McCready, , 1985McCready, , 1986McKee & Welch, 1989, 1992Ono, 1966;Over, 1960;Plug & Ross, 1994;Reid, 1813;Rock & McDermott, 1964;Sedgwick, 1986;Sedgwick & Nicholis, 1993). Researchers have also...…”
Section: Appendix: Projected Versus Distal Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…This distal versus projected distinction has been made often in the visual perception literature (Arend & Goldstein, 1990;Carlson, 1960;Changizi & Widders, 2002;Gibson, 1950;Gilinsky, 1955;Gillam, 1998;Mack, 1978;Palmer, 1999;Rock, 1983;Sedgwick & Nicholis, 1993), and perception of projected size (as opposed to distal size) has been observed a number of times over the history of visual perception (Angell, 1974;Baird, 1968;Biersdorf, Ohwaki, & Kozil, 1963;Carlson, 1960Carlson, , 1962Craig, 1969;Daniels, 1972;Foley, 1972;Gibson, 1950;Gilinsky, 1955;Gogel & Eby, 1997;Jenkin & Hyman, 1959;Joynson, 1949;Kaneko & Uchikawa, 1993, 1997Komoda & Ono, 1974;Leibowitz & Harvey, 1969;Lucas, 1969;Mack, 1978;McCready, 1965McCready, , 1985McCready, , 1986McKee & Welch, 1989, 1992Ono, 1966;Over, 1960;Plug & Ross, 1994;Reid, 1813;Rock & McDermott, 1964;Sedgwick, 1986;Sedgwick & Nicholis, 1993). Researchers have also...…”
Section: Appendix: Projected Versus Distal Propertiesmentioning
confidence: 93%
“…This distal versus projected distinction has been made often in the visual perception literature (Arend & Goldstein, 1990; Carlson, 1960; Changizi & Widders, 2002; Gibson, 1950; Gilinsky, 1955; Gillam, 1998; Mack, 1978; Palmer, 1999; Rock, 1983; Sedgwick & Nicholis, 1993), and perception of projected size (as opposed to distal size) has been observed a number of times over the history of visual perception (Angell, 1974; Baird, 1968; Biersdorf, Ohwaki, & Kozil, 1963; Carlson, 1960, 1962; Craig, 1969; Daniels, 1972; Foley, 1972; Gibson, 1950; Gilinsky, 1955; Gogel & Eby, 1997; Jenkin & Hyman, 1959; Joynson, 1949; Kaneko & Uchikawa, 1993, 1997; Komoda & Ono, 1974; Leibowitz & Harvey, 1969; Lucas, 1969; Mack, 1978; McCready, 1965, 1985, 1986; McKee & Welch, 1989, 1992; Ono, 1966; Over, 1960; Plug & Ross, 1994; Reid, 1813; Rock & McDermott, 1964; Sedgwick, 1986; Sedgwick & Nicholis, 1993). Researchers have also shown that observers make qualitatively very different “size” judgments when given projected size instructions compared to when given distal size instructions (Biersdorf et al, 1963; Carlson, 1960, 1962; Gilinsky, 1955; Jenkin & Hyman, 1959; Leibowitz & Harvey, 1969): For stimuli with cues to the distal size, projected size instructions lead to judgments closely matching projected size, and distal size instructions lead to judgments closely matching distal size.…”
Section: Appendix: Projected Versus Distal Propertiesmentioning
confidence: 99%
“…In a natural outdoor setting, a full moon on the horizon appears often to be more than 1.5 times larger than the moon at the zenith. Many other factors than the state of oculomotor system therefore may contribute to the natural moon illusion (Leibowitz & Owens, 1989; Plug & Ross, 1994; Ross & Plug, 2002). I think, however, that, as shown in my complete darkness and monocular/binocular experiments, the moon illusion per se (i.e., the kernel of this illusion) is principally induced by the binocular state of the oculomotor system.…”
Section: Discussionmentioning
confidence: 99%
“…Kaufman and Rock called the former unconscious distance the "registered" distance to distinguish it from the consciously perceived distance (Kaufman & Rock, 1962a, 1989. This explanation for the apparent distance of the moon has been often referred to as the further-larger-nearer theory (Plug & Ross, 1989).…”
Section: Is the Moon Illusion Really Caused By The Size-distance Invamentioning
confidence: 99%
See 1 more Smart Citation